Music of the Great Depression - Young, William H., 1939-; Young, Nancy K., 1940-; ebrary, Inc. (Westport, Conn. : Greenwood Press, 2005)
Prior to the stock market crash of 1929 American music still possessed a distinct tendency towards elitism, as songwriters and composers sought to avoid the mass appeal that critics scorned. During the Depression, however, radio came to dominate the other musical media of the time, and a new era of truly popular music was born. Under the guidance of the great Duke Ellington and a number of other talented and charismatic performers, swing music unified the public consciousness like no other musical form before or since. At the same time the enduring legacies of Woody Guthrie in folk, Aaron Copeland in classical, and George and Ira Gershwin on Broadway stand as a testament to the great diversity of tastes and interests that subsisted throughout the Great Depression, and play a part still in our lives today. The lives of these and many other great musicians come alive in this insightful study of the works, artists, and circumstances that contributed to making and performing the music that helped America through one of its most difficult times. This volume in the new American History through Music reference series examines how popular music came to the fore during the Great Depression and explores the lives of the great musicians who contributed to making and performing the music that helped America through one of its most difficult times.
Music and media : radio, sheet music, and recordings -- Popular hits and standards -- Music from Broadway and Hollywood -- The rise of swing and the triumph of big bands -- Roots music -- The classical tradition and the Federal Music Project -- Outstanding musical artists from the 1930s.
Description based on print version record.
Includes bibliographical references (p. [253]-260) and indexes.
Electronic reproduction.
Keywords: Popular music -- United States -- 1921-1930 -- History and criticism; Popular music -- United States -- 1931-1940 -- History and criticism; Depressions -- 1929 -- United States